Stability of a Floating Fiber Levee Model on Coastal Areas in Response to Climate Change - Sunaryo; Slamet Imam Wahyudi; Moh. Faiqun Ni'am; Adam Safitri (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study aimed to analyze the stability and performance of a floating fiber levee model in response to hydrostatic pressure, shear forces, and overturning moments under three different water level scenarios. The methodology involved experimental testing in a laboratory using a floating fiber levee model placed in a water-filled test tank, as well as numerical simulations conducted with ANSYS software to analyze the structural behavior of the levee. The results showed that although there were minor differences between the experimental and numerical simulation outcomes, both approaches provided consistent results regarding the stability and resistance of the levee against hydrostatic pressure and other forces. In all scenarios, the floating fiber levee model showed good stability, with adequate safety factors against shear forces, overturning moments, and buoyant forces. This research contributed to the understanding of fiber composite use in more environmentally friendly and efficient coastal levee construction, and opened up potential for further development in managing coastal infrastructure that is adaptive to climate change. Further studies were recommended to evaluate the application of this model on a larger scale and under more varied conditions.